Association Between Peripartum Hysterectomy and Venous Thromboembolism. Issue 4 (21st December 2022) - Mauney, L.; Barth, W.; Clapp, M.
Abstract : ( Am J Obstet Gynecol . 2022;226:119.e1) While venous thromboembolism (VTE) during pregnancy is uncommon, it accounted for 9.2% of all maternal deaths. Previous studies determined augmenting factors such as maternal age, obesity, thrombophilia, tobacco use, obstetrical risk factors, length of surgery, and childbirth.